ผลของโปรแกรมการสอนแนะต่อการปฏิบัติการช่วยฟื้นคืนชีพขั้นพื้นฐานของมารดาที่มีบุตรป่วยด้วยโรคหัวใจพิการแต่กำเนิด - สุพีระพรรณ ธูปมงคล (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The purpose of this quasi-experimental research was to study the effect of coaching on practice for basic cardiopulmonary life support in mothers of congenital heart disease children. The participants consisted of 40 mothers of congenital heart disease children at out-patient and in-patient department, Queen Sirikit National Institute of Child Health. The mothers were divided into the experimental and control group for 20 people in each group. The mothers in both groups were similar in age, educational level, and the experience of basic cardiopulmonary life support. The control group received the conventional nursing care. The experimental group received coaching on practice of basic cardiopulmonary life support program based on the coaching concept of Gracy (2001). The instruments were a set of questionnaires, comprised of demographic characteristics, the competency evaluation: basic life support based on American Heart Association (2006). The program and the competency evaluation: basic life supports were tested for content validities by five panel of experts, and the reliability for the competency evaluation was .86. The data were analyzed by using percentage, mean, standard deviation, and t-test. The major findings were as follows : 1. The practice skill of mothers with congenital heart disease children after received coaching on practice of basic cardiopulmonary life support program was significantly higher than before receiving the program at a level of .05. 2. The practice skill of mothers with congenital heart disease children who received coaching on practice of basic cardiopulmonary life support program was significantly higher than those who receiving conventional nursing care at a level of .05.